2009
DOI: 10.1002/jmv.21398
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene transcription in sera during chronic hepatitis C infection

Abstract: Alternative, non-invasive techniques are necessary to monitor the progression of liver disease during chronic hepatitis C. Firstly, because serum is the most accessible material for studies using qPCR in microplates, gene transcription was compared in 219 selected genes involved in the pathogenesis of hepatitis C virus (HCV) infection between sera, PBMCs and liver samples collected simultaneously from five patients infected chronically. Secondly, using sera, gene profiles were compared between HCV-infected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…In addition, our collaboration with Herv e Groux, who has described two specific markers of the Tr1 cell subpopulation, allowed us to verify for the first time the implication of these regulatory T cells in HL (Rahmoun et al, 2006). Indeed, others, as well as our group have confirmed that the specific expression of two integrins (ITGB2 ITGA2) on CD4 + T cells characterizes the Tr1 cell subpopulation (Rahmoun et al, 2006;Carpentier et al, 2009). In the present study, quantitative gene and protein expressions of ITGB2 and ITGA2 was significantly increased in tumour biopsy samples of EBVpositive HL patients.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, our collaboration with Herv e Groux, who has described two specific markers of the Tr1 cell subpopulation, allowed us to verify for the first time the implication of these regulatory T cells in HL (Rahmoun et al, 2006). Indeed, others, as well as our group have confirmed that the specific expression of two integrins (ITGB2 ITGA2) on CD4 + T cells characterizes the Tr1 cell subpopulation (Rahmoun et al, 2006;Carpentier et al, 2009). In the present study, quantitative gene and protein expressions of ITGB2 and ITGA2 was significantly increased in tumour biopsy samples of EBVpositive HL patients.…”
Section: Discussionmentioning
confidence: 80%
“…Four IgG subclasses (IgG1 to IgG4) differ in their heavy chain constant regions and have different effects on virus-cell fusion inhibition, virus neutralization, and overall course of infection, as have been reported for various viruses including HIV [30] and HBV [31]. Highly expressed proteins encoding heavy chains for immunoglobulins including IGHG1, IGHG3, IGHG4, and IGH@ have been reported with upregulation in HBV [32, 33] and HCC patients [34]. Other upregulated protein families such as heat shock protein, histone, ras-related protein, and von Willebrand factor identified in current study have also been reported in patients infected by HBV or hepatitis C virus (HCV) [35–38].…”
Section: Resultsmentioning
confidence: 99%
“…However, we can assume that this correlation exists, since we published a previous study in which gene transcription was compared in 219 selected genes involved in the pathogenesis of HCV infection between sera, PBMCs, and liver samples collected simultaneously from five patients infected chronically. After amplification, significant correlations were observed between liver versus serum; liver versus PBMCs; and serum versus PBMCs [31]. In addition, a prospective trial is currently under way to confirm these data and to add functional assays, but the results will not be available for several years.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis was performed on serum samples, PBMCs, and biopsies; using this technique on a large panel of genes, we had previously found a correlation between the liver, PBMC, and serum regarding the transcription of 219 genes [31]. Serum samples were analyzed at baseline, before the beginning of the treatment, at 12 months (end of the course of ribavirin and pegylated interferon), at 18 months, and at 30 months (6 months after the end of second therapeutic cycle) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%